PENGARUH MEDIA PEMBELAJARAN INTERAKTIF ANDROID TERHADAP MINAT SISWA PADA MATERI REAKSI REDUKSI OKSIDASI - Tarsha, Cindy Fellya; Refelita, Fitri; Yenti, Elvi (Journal of Chemistry Education and Integration, 2024)
AbstractThis research was instigated by Senior High School students who were not interested in Chemistry subject, so the efforts to increase student interest were needed, one of which was by using Android based interactive learning media. This research aimed at finding out the effect of using Android based interactive learning medium toward student learning interest on Oxidation Reduction Reactions lesson at Sport State Senior High School Riau Province. The use of Android based interactive learning medium was expected able to improve chemistry learning more interesting and effective. Quantitative approach was used in this research with quasi-experiment method and pretest-posttest design. Total sampling technique was used in this research, the tenth-grade students of Natural Science 2 were as the experiment group, and the students of Natural Science 1 were as the control group. The data of student learning interest were obtained by using questionnaire instrument and analyzed by using t-test and determination coefficient to find out the effect on student learning interest in the significance score. Based on the results obtained, the score of tobserved was 6.061, sig 2-tailed was 0.000, and ttable was 2.018. If the significance score 0.000 was lower than 0.05 and the score of tobserved was higher than ttable, it could be concluded that Null hypothesis (H0) was rejected and Ha was accepted. It meant that there was a significant effect of using Android based interactive learning medium toward student learning interest with the effect coefficient 16.4%. Keywords : Android Based Interactive Learning Media, Learning Interest, Oxidation Reduction Reactions